2011
DOI: 10.1111/j.1365-3091.2011.01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Tempestite facies models for the epicontinental Triassic carbonates of the Betic Cordillera (southern Spain)

Abstract: This study focuses on storm deposits in the Muschelkalk facies of the Betic Cordillera (southern Spain) and interprets their deposition mechanisms. Three types of storm deposit are distinguished: (i) pot/gutter casts; (ii) tempestite beds; and (iii) storm-winnowed deposits. Each deposit provides information about the carbonate platform environment in which it was deposited. The tempestite models proposed are: (i) the bypass-zone tempestite model, occurring in a muddy ramp at the epicontinental basin margin. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…Bivalve coquinas with internal erosional surfaces are interpreted as tempestites (Schlaf 1996;Pérez-López & Pérez-Valera 2012), and they support the idea of an episodically high-energy environment above the storm wave base, whereas the fossil assemblage suggests normal marine conditions. A nearshore, shallow water depositional setting was suggested by De Zanche et al (2000) for the Tor Formation at Cave del Predil.…”
Section: Tor Formationmentioning
confidence: 92%
“…Bivalve coquinas with internal erosional surfaces are interpreted as tempestites (Schlaf 1996;Pérez-López & Pérez-Valera 2012), and they support the idea of an episodically high-energy environment above the storm wave base, whereas the fossil assemblage suggests normal marine conditions. A nearshore, shallow water depositional setting was suggested by De Zanche et al (2000) for the Tor Formation at Cave del Predil.…”
Section: Tor Formationmentioning
confidence: 92%
“…Recently, MacEachern et al (2012) and suggested that it characterizes mainly the Glossifungites ichnofacies. B. triadicus is common in carbonates of very shallow to intertidal marine environments (Knaust 1998;Pérez-López and Pérez-Valera 2012).…”
Section: Archaeonassa Fossulatamentioning
confidence: 99%
“…However, a few reports on the Middle Triassic carbonate successions of Germany (e.g. Knaust 1998Knaust , 2007a, southern Spain and Italy (Sardinia) (Rodríguez-Tovar et al 2007;Rodríguez-Tovar and Pérez-Valera 2008;Knaust and Costamagna 2012;Pérez-López and Pérez-Valera 2012) were published recently.…”
mentioning
confidence: 99%
“…Current induced alignment, winnowing and earth quakes or storm events (Aigner 1985;Brett & Baird 1986;Seilacher & Aigner 1991;Hips 1998;Radley & Barker 1998;Storms 2001;Pérez-Lopéz & Pérez-Valera 2012) are discussed as trigger factors for such gravity forced 'event beds'. The described examples are thus autocyclic (Einsele et al 1991b), formed by nonperiodic mass flows and/ or turbidites endemic to the tectonic setting (Bouma et al 1982;Cook et al 1982;Howell & Normark 1982;Tucker & Wright 1990;Potter et al 2005;Hornung 2008).…”
Section: The Kasimlarceltites Mass Occurrence As An Abundance Zonementioning
confidence: 99%
“…debris flows, grain flows or turbidity currents; Middleton & Hampton 1973, 1976Flügel 1978Flügel , 2004Lowe 1982 Kawakami & Kawamura 2002;Potter et al 2005;Nichols 2009;SEPM 2014), also termed gravity flows or density currents, will be discussed in respect to resedimentation of sediments and biogenic components. The determination of specific mechanisms in terms of the genesis concerning event bed deposition, storm deposition, shell accumulation and the consequences for the facies and bioclastic fabric were reported and discussed in Aigner (1982aAigner ( , 1985, Einsele & Seilacher (1982), Kreisa & Bambach (1982), Brett & Baird (1986), Kidwell (1986Kidwell ( , 1991aKidwell ( ,b, 1993a, Kidwell et al (1986), Tucker & Wright (1990), Brett & Seilacher (1991), Chuanmao et al (1993), Einsele et al (1991a,b), Seilacher & Aigner (1991), Soja et al (1996), Hips (1998), Fürsich & Pandey (1999), Martin (1999), Storms (2001), Lukeneder (2003aLukeneder ( ,b, 2004a, Fernández-López (2007), Montiel-Boehringer et al (2011), andPérez-Lopéz &Pérez-Valera (2012). The result is a detailed succession of abundance or accumulation layers (i.e.…”
Section: Introductionmentioning
confidence: 99%